el-Kâmil fi’t-târîh - 880-01 İbnü'l-Esîr, İzzeddin, 1160-1233. (Beyrut Beyrut Beyrut)
13 cilt (1. c. 697 sayfa, 3 yaprak ; 2. c. 579 sayfa, 3 yapyak ; 3. c. 537 sayfa, 3 yaprak ; 4. c. 602 sayfa, 3 yaprak ; 5. c. 629 sayfa, 2 yaprak ; 6. c. 545 sayfa, 2 yaprak ; 7. c. 570 sayfa, 3 yaprak ; 8. c. 734 sayfa, 3 yaprak ; 9. c. 676 sayfa, 3 yaprak ; 10. c. 711 sayfa, 3 yaprak ; 11. c. 585 sayfa, 3 yaprak ; 12. c. 522 sayfa, 3 yaprak ; 13. c. 550 sayfa)